A computational approach for the lifetime prediction of cardiovascular balloon-expandable stents. (June 2015) - Auricchio, F.; Constantinescu, A.; Conti, M.; Scalet, G.
Highlights: Numerical fatigue-life assessment of cardiovascular balloon-expandable stents. General fatigue prediction methodology for classic coronary stent design. Adoption of a global computational approach composed of mechanical-fatigue analyses. Use of fatigue criteria calibrated on appropriate experimental data. Abstract: This paper presents a methodology for the numerical fatigue-life assessment of cardiovascular balloon-expandable stents. The methodology is based on a global computational approach composed of a mechanical finite element analysis, followed by a fatigue analysis. The method is applied to a classical 316L stainless steel coronary stent design (i.e., the Medinol/Boston Scientific NIR™ stent). Fatigue criteria based on elastic and plastic shakedown concepts for finite and infinite lifetime are used to predict fatigue crack initiation and are calibrated on experimental data related to 316L stainless steel μ m-size components, manufactured as stents. The results from the fatigue analysis allow to discuss several aspects affecting stent lifetime, such as the applied cyclic loading including systolic–diastolic pressurization and bending. The generality of the proposed methodology encourages further investigations of such an approach for its application to other materials or small-scale components.